ANALISIS PERBEDAAN GENDER TERHADAP SIKAP BERKOMPUTER DAN KINERJA MAHASISWA PADA KELAS ERP - fitria melynsyah yusuf (JSAP : Journal Syariah and Accounting Public, 2018)
This study entitled "ANALYSIS OF GENDER DIFFERENCES ON COMPUTER ATTITUDE AND STUDENT PERFORMANCE IN ERP CLASSES (CASE STUDY OF ACCOUNTING STUDENTS FOR 2012-2013 ACADEMIC YEARS)". The purpose of this study is (1) To measure the ability of each gender to absorb computer technology conducted objectively, namely to have data, information, and supporting evidence from related sources or objects.